Modulation of the Expression of the GABAA Receptor β1 and β3 Subunits by Pretreatment with Quercetin in the KA Model of Epilepsy in Mice -The Effect of Quercetin on GABAA Receptor Beta Subunits- - Sahar Moghbelinejad; Zahra Rashvand; Fatemeh Khodabandehloo; Ghazaleh Mohammadi; Marjan Nassiri-Asl (Korean Pharmacopuncture Institute, 2016)
Objectives: Quercetin is a flavonoid and an important dietary constituent of fruits and vegetables. In recent years, several pharmacological activities of quercetin, such as its neuroprotective activity and, more specifically, its anti-convulsant effects in animal models of epilepsy, have been reported. This study evaluated the role of quercetin pretreatment on gene expression of γ-amino butyric acid type A (GABAA) receptor beta subunits in kainic acid (KA)-induced seizures in mice. Methods: The animals were divided into four groups: one saline group, one group in which seizures were induced by using KA (10 mg/kg) without quercetin pretreatment and two groups pretreated with quercetin (50 and 100 mg/kg) prior to seizures being induced by using KA. Next, the messenger ribonucleic acid (mRNA) levels of the GABAA receptor β subunits in the hippocampus of each animal were assessed at 2 hours and 7 days after KA administration. Quantitative real-time polymerase chain reaction (RT-PCR) assay was used to detect mRNA content in hippocampal tissues. Results: Pretreatments with quercetin at doses of 50 and 100 mg/kg prevented significant increases in the mRNA levels of the β1 and the β3 subunits of the GABAA receptor at 2 hours after KA injection. Pretreatment with quercetin (100 mg/kg) significantly inhibited β1 and β3 gene expression in the hippocampus at 7 days after KA injection. But, this inhibitory effect of quercetin at 50 mg/kg on the mRNA levels of the β3 subunit of the GABAA receptor was not observed at 7 days after KA administration. Conclusion: These results suggest that quercetin (100 mg/kg) modulates the expression of the GABAA receptor β1 and β3 subunits in the KA model of epilepsy, most likely to prevent compensatory responses. This may be related to the narrow therapeutic dose range for the anticonvulsant activities of quercetin.